Bağımsızlığın 30. Yılında Türk Dünyası Analizleri - Şahin, Köksal (Sakarya Üniversitesi Yayınları, 2023)
Turkic World studies seem to be a topic that attracts scientific attention day by day. The continuous increase in cooperation, rapprochement, and mobility between Turkish-speaking countries and communities since 1991 might be shown as the main dynamic behind this interest. The richness of the Turkic Republics in terms of natural resources, their location on the energy and transportation corridors, the change of the balances in the Caucasus with the Second Karabakh War in 2020, and the transition of the Turkic Council from a cooperation organization to an interstate organization in 2021 under the name of the "Organization of Turkic States" also accelerate the work of the Turkic World. In the meantime, the popularization of some geopolitical determinations and predictions in the context of scientific interest in the region can be shown as an important factor. Similar to the rise of Europe in the industrial age, we can talk about the rise of Asia in the information age. The sources of political and economic power are shifting to Asian geopolitics and this process continues to strengthen. Such analyses and predictions, which bring to the agenda that in the 2050s, Asia will regain its former central position also encourage academic interest in Central Asia. This book is the product of the goal of creating an original work for the Turkish World with gap-filling parameters and process analyses determined by a meticulous preliminary study in the light of the mentioned background. In this direction, three basic perspectives such as the effort to determine the capacities of the countries with comparative analyses, to look at the Turkish World from the perspective of problems, and to embody the Turkish World based on the community, autonomous region, and country sections dominate the work. With comparative analyses, it has been tried to embody the capacities of the countries within the parameters such as sustainable development potential, transportation systems, scientific performance, evolution in the political system, education system, and values of education. On the other hand, the crises affecting the Turkic World were discussed with the analysis of Karabakh, which is the main crisis, and the Russia-Ukraine War, which is the current crisis. On the other hand, the analysis of the thirty-year process in the Turkish World, starting from the scales of the community, autonomous region, and country, was carried out through the examples of Georgia, Tatarstan, and Uzbekistan.